The Health Benefits of Probiotic Lactiplantibacillus plantarum: A Systematic Review and Meta-Analysis - Amal Aljohani; Noha Rashwan; Shruti Vasani; Ahmed Alkhawashki; Tong Tong Wu; Xingyi Lu; Daniel A. Castillo; Jin Xiao (Probiotics and Antimicrobial Proteins, 2025)
To ensure effective administration of probiotics in clinical practice, it is crucial to comprehend the specific strains and their association with human health. Therefore, we conducted a systematic review and meta-analysis to evaluate the scientific evidence on the impact of Lactiplantibacillus plantarum probiotic consumption on human health. Out of 11,831 records, 135 studies were assessed qualitatively, and 18 studies were included in the meta-analysis. This systematic review demonstrated that probiotic supplementation with L. plantarum , either alone or in combination, can significantly improve outcomes for patients with specific medical conditions. Meta-analysis revealed notable benefits in periodontal health, evidenced by reduced pocket depth and bleeding on probing ( p < 0.001); in gastroenterological health, marked by significant reductions in abdominal pain ( p < 0.001); and in infectious disease, through a reduction in C-reactive protein levels ( p < 0.001). Cardiovascular benefits included lowered total cholesterol and low-density lipoprotein cholesterol in the L. plantarum intervention group ( p < 0.05). Our study’s clinical significance highlights the importance of considering probiotic strain and their application to specific diseases when planning future studies and clinical interventions, emphasizing the need for further research in this area.